2022
DOI: 10.1007/s00226-022-01407-9
|View full text |Cite
|
Sign up to set email alerts
|

Semi-supervised learning for quality control of high-value wood products

Abstract: The quality control of wood products is often only checked at the end of the production process so that countermeasures can only be taken with a time delay in the event of fluctuations in product quality. This often leads to unnecessary and cost-intensive rejects. Furthermore, since quality control often requires additional procedural steps to be performed by a skilled worker, testing is time-consuming and costly. While traditional machine learning (ML) methods based on supervised learning have been used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…193 SSL methods are more applicable to real-world applications where unlabeled data is readily available and easy to obtain, while labeled instances are often difficult, expensive, and timeconsuming to collect, which is often the case in wood product manufacturing. For instance, Schubert et al 270 used a particularly small data set to determine the effect of the SSL method label spreading 271 on the performance of algorithms based on random forests (RF) and support vector machines (SVM), two common ML techniques for classification. The work clearly showed that SSL can be used to augment small data sets to improve the generalization ability of ML algorithms such as RF for quality classification of real wood product data.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…193 SSL methods are more applicable to real-world applications where unlabeled data is readily available and easy to obtain, while labeled instances are often difficult, expensive, and timeconsuming to collect, which is often the case in wood product manufacturing. For instance, Schubert et al 270 used a particularly small data set to determine the effect of the SSL method label spreading 271 on the performance of algorithms based on random forests (RF) and support vector machines (SVM), two common ML techniques for classification. The work clearly showed that SSL can be used to augment small data sets to improve the generalization ability of ML algorithms such as RF for quality classification of real wood product data.…”
Section: Chemical Reviewsmentioning
confidence: 99%